Development of Inquiry Materials Based on Chemical Representation to Improve Students’ Critical Thinking Ability (Journal of Innovative Science Education, 2019)
Twenty first century learning directs teachers and students to develop learning to promote critical thinking skills. The learning model accommodating critical thinking skills is inquiry. Chemistry learning modules that have not used a chemical representation approach. This study aims to produce chemical representation based equilibrium modules with a decent and quality inquiry approach. This research is a development research from Thiagarajan modified 4D model. Four stages of development are Define (design), Design (Develop), Develop (development), and Disseminate (spread), with disseminate not done. Evaluation of module feasibility is seen from the validity and effectiveness of the module. The effectiveness of the module is seen from the increase in learning outcomes and improvement of students' critical thinking skills. Based on the results of the analysis obtained a validity value of 3.41 (85.25%) with a very good category. In a large-scale trial obtained an increase in learning outcomes through the N-Gain test obtained an average value of 0.72 with a high category, while the aspect of critical thinking was assessed based on observations on the observations and explanations of students in answering questions. Critical thinking ability of students at a score of 3.35 with a good predicate. While the response of students who agreed to use the chemical module was 96%. The average score of posttest using critical thinking questions is 81.39. Based on the results of the evaluation of inquiry-based chemical equilibrium material modules and the chemical representation approach it is said to be feasible and effective for learning.